The Influence of Financial Literacy, Social Interaction, and Herding Behavior on Financial Investment Intention with Risk Tolerance as a Mediating Variable - Sandhy Bayu Putra; Pambuko Naryoto (Yayasan Riset dan Pengembangan Intelektual, 2026)
This study aims to examine the effects of financial literacy, social interaction, and herding behaviour on investment intention, with risk tolerance acting as a mediating variable. The study is motivated by the rapid growth of investors in Indonesia, which has not been accompanied by adequate financial knowledge and rational investment behavior. A quantitative research approach was employed using a survey method. Data were collected through structured questionnaires distributed to individuals with investment experience or interest in Jakarta and surrounding areas. The sampling technique applied was purposive sampling, and data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results indicate that financial literacy and social interaction have a positive and significant effect on investment intention. Herding behaviour also shows a significant influence on investment intention, although it tends to encourage less rational investment decisions. Furthermore, financial literacy and social interaction positively affect risk tolerance, while herding behaviour negatively influences risk tolerance. Risk tolerance has a significant effect on investment intention and mediates the relationship between financial literacy, social interaction, herding behaviour, and investment intention. This study provides empirical insights for strengthening financial education programs and promoting rational and sustainable investment behavior.